Applicability of traditional and advanced methods for oxidative quality and stability on marine phospholipids. Issue 3 (5th August 2016) - Mozuraityte, Revilija; Kristinova, Vera; Standal, Inger Beate; Evensen, Henning; Rustad, Turid
Abstract : The objective of this study was to evaluate oxidative status and stability measurements of cod roe phospholipid (PL) extracts obtained by different extraction methods, and of two refined fish oils. The oxidative status varied depending on the method and on the extraction methods for the PL extracts. Peroxide value (PV) and anisidine value (AV) were not measurable in PL extracted by ethanol due to dissolution issues and precipitation occurring in the reaction mixture, the latter were attributed to co‐extracted compounds. The thiobarbituric acid reactive substances (TBARS) values were significantly lower for determinations in the presence of an antioxidant in the reaction mixture for both fish oils and PL indicating that marine lipids may become oxidized in the course of the analysis. The accelerated oxidation revealed major differences in the pattern of oxidation in bulk fish oil and bulk PL. While for fish oils, the level of omega‐3 fatty acids decreased and the level of both peroxides and aldehydes increased, PL showed minor loss of omega‐3 fatty acids, minimal presence of the oxidation markers accompanied by disappearance of phosphatidylethanolamine group. This study shows that the applicability of classical oxidation status methods on marine phospholipids is limited. Variations in the methods, such as the choice of lipid solvent/reaction medium, may also lead to different results. 1 H high resolution magnetic resonance spectroscopy NMR proved to be a valuable tool to study the different oxidation patterns of fish oils and PLs. Practical applications: The oxidative status and stability of marine omega‐3 lipids are important quality parameters. The marine lipid industry usually relies upon two standard analyses to describe the quality of their products: PV by the AOCS Official method Cd 8b‐90 and AV by the AOCS Official Method Cd 18–90. This work studies the applicability of these traditional and other methods to describe oxidative status and stability of marine phospholipids compared to classical fish oils. The results show that depending on the processing and composition, some of the methods are not applicable for phospholipids and, therefore, can give a misleading picture of the quality of the product. Moreover, the paper also shows that oxidative pathway for phospholipids are different compared to triacylglycerides and that an analytical tool like NMR can be used to describe the quality of marine phospholipids. 1 H NMR results show that different oxidation patterns are involved during oxidation of marine phospholipids compared to marine oils (cod liver oil) and this can also limit acceptability of standard oxidative quality and stability methods for marine phospholipids. Abstract : 1 H NMR results show that different oxidation patterns are involved during oxidation of marine phospholipids compared to marine oils (cod liver oil) and this can also limit acceptability of standard oxidative quality and stability methods for marine phospholipids.